AWP1 Restrains the Aggressive Behavior of Breast Cancer Cells Induced by TNF-α - Kim, Eun-Young; Kim, Ji-Eun; Choi, Bongkun; Kweon, Jiyeon; Park, Si-On; Lee, Hee-Seop; Lee, Eun-Jin; Oh, Soyoon; Shin, Ha Rim; Choi, Hyuksu; Kim, Yongsub; Chang, Eun-Ju (Frontiers in Oncology, 2021)
TNF-α plays a crucial role in cancer initiation and progression by enhancing cancer cell proliferation, survival, and migration. Even though the known functional role of AWP1 (zinc finger AN1 type-6, ZFAND6) is as a key mediator of TNF-α signaling, its potential role in the TNF-α-dependent responses of cancer cells remains unclear. In our current study, we found that an AWP1 knockdown using short hairpin RNAs increases the migratory potential of non-aggressive MCF-7 breast cancer cells with no significant alteration of their proliferation in response to TNF-α. A CRISPR/Cas9-mediated AWP1 knockout in MCF-7 cells led to mesenchymal cell type morphological changes and an accelerated motility. TNF-α administration further increased this migratory capacity of these AWP1-depleted cells through the activation of NF-kB accompanied by increased epithelial-mesenchymal transition-related gene expression. In particular, an AWP1 depletion augmented the expression of Nox1, reactive oxygen species (ROS) generating enzymes, and ROS levels and subsequently promoted the migratory potential of MCF-7 cells mediated by TNF-α. These TNF-α-mediated increases in the chemotactic migration of AWP1 knockout cells were completely abrogated by an NF-κB inhibitor and a ROS scavenger. Our results suggest that a loss-of-function of AWP1 alters the TNF-α response of non-aggressive breast cancer cells by potentiating ROS-dependent NF-κB activation.